Contact Lens Study - Spear, V.G. (Canadian Journal of Optometry, 2026)
The pe1formance of two gas permeable contact lens materials was monitored over a two month period (Alcoperm 39 and Fluorperm 40). It was found that both lenses performed well with the fluorocarbon material having some slight advantages.